Uptake of exemestane chemoprevention in postmenopausal women at increased risk for breast cancer - Aktas, Bilge (Eur J Cancer Prev, 2016)
Despite their efficacy, uptake of selective estrogen receptor modulators for breast cancer chemoprevention remains low. Exemestane, an aromatase inhibitor, has recently been identified as a potential chemopreventive option with fewer serious side effects compared with selective estrogen receptor modulators in postmenopausal women. The purpose of this study was to assess the uptake of exemestane in a breast cancer prevention clinic. A retrospective chart review was conducted to capture chemoprevention uptake by postmenopausal women presenting to the Yale Breast Cancer Prevention Clinic between November 2011 and November 2012. Descriptive statistics of the study population have been presented. Statistical analyses were carried out using SAS 9.3 (SAS Institute Inc., Cary, North Carolina, USA) between December 2012 and February 2013. Of 90 postmenopausal women, 56 were eligible for chemoprevention. Their mean age was 56.8 years. Among the women, 39% had osteopenia or osteoporosis. Thirteen women chose to start chemoprevention medication (23%). Although 31% of the chemopreventive medication administered included exemestane, only four of 56 postmenopausal women opted for exemestane (7%). Chemoprevention uptake rates of postmenopausal women in the setting of a breast cancer prevention clinic are higher than that reported in the general population; however, they remain low overall despite the inclusion of exemestane as an option. A significant proportion of postmenopausal women have decreased bone density, which is a potential barrier to exemestane uptake. The results provide practical implications suggesting that exemestane may have limited impact on breast cancer chemoprevention uptake. Further investigations should focus on understanding the factors that influence, predict, and increase chemoprevention uptake.